Исследование современных методов генерации простых чисел, ключей и схем цифровой подписи для метода RSA - Качко, Е. Г. (ХНУРЭ, 2008)
Research of methods of generation of prime numbers is executed, key information and charts of digital signature in accordance with the standard of FIPS PUB 1863, adding to him and PKCS #1 v2.1 on calculable complication. Formulated recommendation on application of different algorithms and charts.
Keywords: генерация простых чисел; цифровая подпись